Pengaruh Pemberian Terapi Murottal Al-Qur'an Terhadap Waktu Pulih Sadar Pasien Kanker Payudara Dengan Anestesi General Di RSUD Dr. Moewardi Surakarta - Billah, Moh. Al Khoif, Arina Maliya, S.Kep., M.Si., Med, Sahuri Teguh K., S.Kep., Ns., CWCS (2015)
General anesthesia is one of process surgery to relieve pain and patient awareness. Anesthesia technic anddose of medication can affect in recovery timeconsciousof cancermammae patients. Murottal Qur'antheraphy is one of the complementary therapies that can provide comfort and relax. The aim of this study was toexplain the effect ofmurottal Qur'antheraphyon revovered time consciou in cancer mammae with general anesthesia patientsDr. Moewardi Hospital at Surakarta. This study was using quasi experiment with non-equivalent control group design.Samples were 15 respondent of control group and 15 respondent of treatment group (with murottal al-qur'an therapy) cancer mamae with general anesthesia patients with accidental sampling technique.Samples were provide murottal Qur'antheraphy Surah Ar-Rahman with for 15 minutes, after that it's measurerecoveredtime conscious by Aldrete score. The results were analyzed by independent sample t-test. The Result of statisfical had significant value (p-value) 0.036 (p <0.05), so there was the effect of murottal al-qur'an therapy on revovered time conscious in cancer mamae with general anesthesia patients Dr. Moewardi Hosital at Surakarta . The average recovered time conscious cancer mamae in traetment group was 5, 61 minutes and avarage recovered time conscious cancer mamae in control group was 6, 42 minutes. The conclusion of this study that murottal al-qur'an therapy was effective of revovered time conscious in cancer mamae with general anesthesia patient Dr. Moewardi hospital at Surakarta.